1970
DOI: 10.1037/h0028638
|View full text |Cite
|
Sign up to set email alerts
|

Ingredients of successful treatment programs for underachievers.

Abstract: Twenty-three studies were reviewed that evaluated the effectiveness of various treatment programs for underachieving college students. All of the studies used grade-point average as the dependent variable, and a specific treatment program intended to improve student academic performance as the independent variable. The results of the survey indicate that the treatment programs associated with improved student academic performance were characterized as (a) structured rather than unstructured, (b) lengthy rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

1972
1972
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 17 publications
(3 reference statements)
3
42
0
Order By: Relevance
“…Much of the research reports positive effects on the academic performance of students involved. However, there is general agreement among earlier reviews that these effects have been modest and short-lived (Bednar and Weinberg, 1970;Behrman et al, 1984;Entwisle, 1960). Behrman et al (1984) attribute limitations within the learning-skills intervention literature to several factors.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Much of the research reports positive effects on the academic performance of students involved. However, there is general agreement among earlier reviews that these effects have been modest and short-lived (Bednar and Weinberg, 1970;Behrman et al, 1984;Entwisle, 1960). Behrman et al (1984) attribute limitations within the learning-skills intervention literature to several factors.…”
Section: Introductionmentioning
confidence: 89%
“…Major reviews of the academic competence literature (Bednar and Weinberg, 1970;Entwisle, 1960;Kirschenbaum and Perri, 1982;Mitchell and Piatkowska, 1974) have led to some confusion regarding the efficacy of intervention programmes. Much of the research reports positive effects on the academic performance of students involved.…”
Section: Introductionmentioning
confidence: 99%
“…Counselors have attempted varied interventions to improve the academic effectiveness and productivity of underachieving college students, defined as those who perform significantly below expected performance as measured by scholastic aptitude tests (Bednar & Weinberg, 1970;Decker & Russell, 1981;Greiner & Karoly, 1976). Given the large number of students who drop out of college or who are in academic difficulty each year, the development and evaluation of effective and economical interventions for underachievers seems crucial.…”
Section: Multicomponent Groupmentioning
confidence: 99%
“…anxiety of underachievers (Bednar & Weinberg, 1970;Mitchell & Piatrowska, 1974b). A second approach, based on the assumption that such anxiety inhibits test performance, has been directed toward reducing anxiety elicited by the testing situation.…”
mentioning
confidence: 99%
“…Continued evaluation of this process in various settings may well indicate a need to reorient thinking relative to the practice of complete reliance on individual counseling. Bednar and Weinberg (1970) reviewed 23 studies in individual and group counseling. They found that of fourteen studies using group counseling, nine showed significant improvement in grade point average while two of seven studies using individual counseling reported a significant improvement.…”
mentioning
confidence: 99%